The role of academic literacy courses in students' disciplinary knowledge-building: a case study of a Namibian university - Nekondo, Linus Vaakohambo (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning)
This doctoral study investigated the role of academic literacy courses in shaping students' disciplinary knowledge within the context of a Namibian university. Motivated by concerns surrounding persistently high attrition rates in higher education institutions globally, the research challenges the prevailing tendency to attribute poor student performance solely to individual factors, thus neglecting systemic issues whereby the higher education sector is absolved of responsibility. This absolution is often on the premise that the university has provided adequate support, such as through academic literacy courses, to equip students for success. However, despite the provision of such courses, high attrition rates persist. The study was guided by the following questions: 1. How is 'academic literacy' conceptualised in the UNAM English for Academic Purposes course curriculum? This question is further divided into two sub-questions: (a) How do the academics who teach the UNAM EAP course conceptualise 'academic literacy'? and (b) How is knowledge structured in course documents and assessments? 2. How do academics who teach other courses conceptualise UNAM's EAP course and its relationship to the literacy practices expected in their courses? 3. How do students experience the EAP course at UNAM, and how do they understand the relationship between the content and activities of the EAP course and the academic literacy demands of their other courses? Data collection involved individual interviews with both English for Academic Purposes (EAP) lecturers and discipline-specific lecturers across three UNAM campuses, the Faculty of Education, Faculty of Engineering and Faculty of Health Sciences. Additionally, focus group interviews were conducted with students from these same campuses. To ensure robustness, triangulation of interview data was achieved by complementing it with document analysis of EAP course materials and mainstream course documents. The goal was to identify instances of code-matches (where academic literacy practices align with the expectations of the disciplines) or code-clashes (where discrepancies emerge). The findings illuminated prevailing perceptions of academic literacy as a set of skills encompassing reading, writing, and related competencies. Implicit in this understanding was that these presumed academic skills are universally applicable across academic contexts and can be taught with equal effectiveness to students regardless of their chosen discipline. An analysis using Legitimation Code Theory (LCT) revealed that such conceptualisation of academic literacy as practices that are neutral and generic across the academy indicates weaker epistemic relations (ER-), and weaker social relations (SR-). That is, the understanding of academic literacy that dominated in the data legitimated neither specialist knowledge nor any specific disposition in the knower. This results in what is known in LCT as a relativist code. Moreover, the study identified a distinct emphasis on generic, skill-based instruction in the EAP course documents. The relativist code identified in the analysis of the interviews with EAP lecturers, and echoing concerns raised in academic literacy literature about add-on courses, was starkly evident in the EAP course content. A code-clash emerged between the skills and genres taught in the EAP course and those required for success in mainstream courses. Three focus areas of the EAP course, essay writing, report writing, and referencing, were analysed in some depth to ascertain the nature of the code-clash. The thesis presents a comprehensive examination of a specific course and its reflection of prevalent generic common-sense approaches observed in various contexts. While the study centred on UNAM's EAP course, its aim was not to critique a particular course or colleagues. Rather, many findings resonate with issues identified in academic literacy research globally, underscoring persistent challenges associated with generic approaches that often fall short of enhancing epistemic access. The study concludes that there is an urgent need to assess the efficacy of academic literacy courses in fostering students' disciplinary knowledge-building at grassroot level i.e. at the level of HEIs or disciplines. Such an assessment should consider not only the complexities of acquisition of academic literacy but also the broader global elements with transboundary influences, such as neoliberalism, massification, and the globalisation of higher education. This comprehensive examination contributes to ongoing discussions regarding the enabling of epistemic access and epistemic justice within higher education contexts.
Keywords: Information literacy; Communication in learning and scholarship; Decolonization-- Namibia; Globalization; Education and globalization-- Namibia; Academic English; Academic language